Uji Heterosis Hibrida F1 dan F1R Hasil Persilangan Dua Jenis Tanaman Jagung (Zea mays, L) - Lauterboom, Daniel Peter (AGRICOLA, 2020)
Heterosis indication for high yield in F1 offspring has a very important meaning in the formation of hybrid varieties of corn (Zea mays L.). Through artificial hybrid between the parents, it can be found out the potential of a hybrid combination result, the value of heterosis, and the combined power. Hybrids between a few lines or corn varieties are to obtain a new hybrid with superior character compared to its parents which are expected to have high heterosis value. This research aims to find out heterosis value of some quantitative characters of F1 and F1R; a hybrid of two species of corn. It is conducted at Doyo Lama Village, Waibu Sub-district, Jayapura District, from October 2018 to August 2019. The research method is an experimental method in which the research consists of two stages; (1) experiment 1: hybrid between parents using single cross of hybrid method towards 2 genotypes of corn parents (J-Doyo 1 and J-Arso 1)to produce 2 genotypes of hybrid: F1 and F1R. (2) experiment 2: genetic evaluation to presume heterosis value from the character being studied. The findings reveal that F1 hybrid of JH-Arsol male x Doyol female has superiority for all characters compared to both parents, such as cobs length is 18,07 cm, cobs diameter is 5,10 cm, the number of rows of seeds per cob is 13,67 rows of seeds. Meanwhile, F1R JH hybrid of JH-Arsol female x Doyol male has superiority for all characters compared to both parents, such as cobs length is 22,93 cm, cobs diameter is 4,73 cm, the number of rows of seeds per cob is 13,00 rows of seeds. The offspring of F1 and F1R hybrid has more superiority than the parents, which is shown by positive heterosis value for all characters being studied.